2015
DOI: 10.1186/s13071-015-1100-2
|View full text |Cite
|
Sign up to set email alerts
|

Eco-epidemiological study of an endemic Chagas disease region in northern Colombia reveals the importance of Triatoma maculata (Hemiptera: Reduviidae), dogs and Didelphis marsupialis in Trypanosoma cruzi maintenance

Abstract: BackgroundIn Colombia, Rhodnius prolixus and Triatoma dimidiata are the main domestic triatomine species known to transmit T. cruzi. However, there are multiple reports of T. cruzi transmission involving secondary vectors. In this work, we carried out an eco-epidemiological study on Margarita Island, located in the Caribbean region of Colombia, where Chagas disease is associated with non-domiciliated vectors.MethodsTo understand the transmission dynamics of Trypanosoma cruzi in this area, we designed a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 53 publications
8
78
1
5
Order By: Relevance
“…We observed a high invasion of domestic ecotopes by this species (Fig. 2), consistent with other studies in Colombia, Brazil and Venezuela where this species even presents morphological and genetic changes across individuals collected in domestic ecotopes [26, 27, 32–34]. Triatoma maculata has not been included in the vector control programs because its diet is mainly composed of bird blood [32, 35–37] and some studies have reported low frequency of infection in Brazil and Venezuela [36, 38].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed a high invasion of domestic ecotopes by this species (Fig. 2), consistent with other studies in Colombia, Brazil and Venezuela where this species even presents morphological and genetic changes across individuals collected in domestic ecotopes [26, 27, 32–34]. Triatoma maculata has not been included in the vector control programs because its diet is mainly composed of bird blood [32, 35–37] and some studies have reported low frequency of infection in Brazil and Venezuela [36, 38].…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, herein the frequency of T. cruzi infection was 67.6% and the percentage of feeding with human blood was 75.0% with the presence of TcIDom in some specimens collected in peridomiciliary habitats. Recent studies in Colombia and Venezuela have revealed infection frequencies between 38.0 and 75.0% and the presence of “TcIb” genotype that is associated with the peridomestic cycle [26, 27, 33, 34, 39, 40]. Regarding the DTUs herein detected, most of the specimens were infected with TcI and TcIII (sylvatic DTUs) and domestic specimens harbored TcIII suggesting how T. maculata can connect domestic and sylvatic transmision cycles (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…En Venezuela T. maculata ha sido considerado tradicionalmente como un vector secundario del agente etiológico de la enfermedad de Chagas, ya que aunque se le ha encontrado infectado naturalmente por T. cruzi, se considera que está adaptado a hábitats peridomiciliarios y silvestres, siendo una especie principalmente ornitófaga, asociada con gallinas y palomas que raramente se alimenta del hombre 2,8 . Sin embargo recientemente ha estado emergiendo un nuevo escenario epidemiológico de esta especie en Venezuela 9-14 y países vecinos como Brasil 15,16 y Colombia 17,18 ya que ha sido encontrada domiciliada y en medios urbanos, lo cual impone la necesidad de revisar el carácter secundario en su capacidad de transmitir al agente etiológico de la enfermedad de Chagas. Pese a que todas las especies de triatominos son potencialmente vectores de T. cruzi 5 , la capacidad vectorial está sujeta a múltiples factores entre los que se encuentran por ejemplo la composición faunística local disponible al insecto, la competencia de transmisión del parásito a mamíferos domésticos, sinantrópicos y silvestres, la tasa de contacto hospedador-vector o la adaptación a diferentes fuentes sanguíneas.…”
Section: Introductionunclassified
“…Studies focusing on the host associations of such species could help to inform policies to limit their impact, for example, by identifying primary vertebrate hosts of sylvatic species. However, most existing studies have focused on known primary vector species and often targeted only domestic or peridomestic habitats where the transmission risk to humans is considered higher (e.g., [40,41] Manuscript to be reviewed broad or specific results for several sets of previously used primers listed in Table 1 (all those listed without asterisks). These primers amplified the corresponding DNA sequence of certain species of Triatominae or did not amplify DNA that should be present based on the results of other primer sets.…”
Section: Introductionmentioning
confidence: 99%